A fully integrated paperfluidic molecular diagnostic chip for the extraction, amplification, and detection of nucleic acids from clinical samples. Issue 4 (20th January 2016) - Rodriguez, Natalia M.; Wong, Winnie S.; Liu, Lena; Dewar, Rajan; Klapperich, Catherine M.
Abstract : We present a low-cost, disposable, and fully-integrated paperfluidic molecular diagnostic chip for sample-to-result functionality at the point-of-care. Abstract : Paper diagnostics have successfully been employed to detect the presence of antigens or small molecules in clinical samples through immunoassays; however, the detection of many disease targets relies on the much higher sensitivity and specificity achieved via nucleic acid amplification tests (NAAT). The steps involved in NAAT have recently begun to be explored in paper matrices, and our group, among others, has reported on paper-based extraction, amplification, and detection of DNA and RNA targets. Here, we integrate these paper-based NAAT steps into a single paperfluidic chip in a modular, foldable system that allows for fully integrated fluidic handling from sample to result. We showcase the functionality of the chip by combining nucleic acid isolation, isothermal amplification, and lateral flow detection of human papillomavirus (HPV) 16 DNA directly from crude cervical specimens in less than 1 hour for rapid, early detection of cervical cancer. The chip is made entirely of paper and adhesive sheets, making it low-cost, portable, and disposable, and offering the potential for a point-of-care molecular diagnostic platform even in remote and resource-limited settings.